Deletion of the Fanconi Anemia C Gene in Mice Leads to Skeletal Anomalies and Defective Bone Mineralization and Microarchitecture. (8th August 2018) - Mazon, Mélody; Julien, Jacinthe; Ung, Roth‐Visal; Picard, Sylvain; Hamoudi, Dounia; Tam, Rose; Filiatrault, Jessica; Frenette, Jérôme; Mac‐Way, Fabrice; Carreau, Madeleine
ABSTRACT: Fanconi anemia (FA) is a rare genetic disorder associated with a progressive decline in hematopoietic stem cells leading to bone marrow failure. FA is also characterized by a variety of developmental defects including short stature and skeletal malformations. More than half of children affected with FA have radial‐ray abnormalities, and many patients have early onset osteopenia/osteoporosis. Although many Fanconi anemia genes have been identified and a molecular pathway defined, the underlying mechanism leading to bone defects remains elusive. To understand the role of FA genes in skeletal development and bone microarchitecture, we evaluated bone physiology during embryogenesis and in adult FancA ‐ and FancC ‐deficient mice. We found that both FancA ‐/‐ and FancC ‐/‐ embryos have abnormal skeletal development shown by skeletal malformations, growth delay, and reduced bone mineralization. FancC ‐/‐ adult mice present altered bone morphology and microarchitecture with a significant decrease in cortical bone mineral density in a sex‐specific manner. Mechanical testing revealed that male but not female FancC ‐/‐ mice show reduced bone strength compared with their wild‐type littermates. Ex vivo cultures showed that FancA ‐/‐ and FancC ‐/‐ bone marrow–derived mesenchymal stem cells (BM MSC) have impaired differentiation capabilities together with altered gene expression profiles. Our results suggest that defective bone physiology in FA occurs in utero and possibly results from altered BM MSC function. These results provide valuable insights into the mechanism involved in FA skeletal defects. © 2018 American Society for Bone and Mineral Research.